A tale of two countries: Spatial and temporal patterns of rice productivity in China and Brazil - You, Liangzhi (International Food Policy Research Institute, 2008)
This paper examines differences in the spatial and temporal variations of rice yields in China and Brazil. Our analysis indicates that, in China, rice yields have converged over time and rice production has become increasingly homogeneous. In contrast, rice yields in Brazil have diverged over time, primarily due to variations in upland rice yields. Three hypothetical explanations may account for the different behaviors of rice yields in Brazil and China, namely: 1) differences in production systems (i.e. irrigated in China vs. upland in Brazil); 2) changes in rainfall patterns; and 3) bias in agricultural research and development (R&D) towards irrigated rice. Our empirical analysis supports the first two hypotheses by establishing that: 1) upland rice shows much more variation in yields compared to irrigated rice; and 2) changing rainfall patterns have primarily affected upland rice. We also provide evidence of the bias towards irrigated systems by looking at the patterns of varietal release.